دور التدقيق في تَطبيق التنمية المُستدامة في الشَركات في ظل معايير التدقيق الدولية - سيف عبد الرزاق محمد الوتار (PROSPECTIVE RESEARCHES, 2023)
After increasing interest in sustainable development, and because companies have a major role in activating sustainable development not only from the financial (economic) side, but also from the social and environmental aspects, it has become imperative for all companies to submit reports on their financial, environmental and social performance, which required the profession of auditing to keep up with progress in The business world to carry out procedures for auditing the financial, environmental and social performance of companies to ensure that they implement sustainable development, hence the importance of research through knowing the role played by auditing in the application of sustainable development based on auditing standards S International, where research aims to find out what is Aolmaeijer that auditors work to carry out control checks for sustainable development reports. Through the research, the major role that the auditor plays when auditing the sustainable development and sustainability reports has been reached in achieving the requirements of sustainable development, in addition to that there are several auditing standards that can guide the performance of the audit of sustainable development.